24. EFEK PENCELUPAN KARKAS AYAM PEDAGING DALAM LARUTAN ASAM ASETAT DAN ASAM SITRAT TERHADAP PENURUNAN KADAR PROTEIN The Effects of Immersion of Broiler Carcass in a Combination of Citric Acid and Acetic Acid on Protein Content - Daniel Sebastian Simangunsong; Nurliana N; Sulasmi S; Ismail I; Teuku Reza Ferasyi; M. Isa (Jurnal Medika Veterinaria, 2016)
The research has been conducted to determine the effect of 3% acetic acid, 3% citric acid, and combination of acetic acid and citric acid, 1.5% each on protein content of broiler carcass. The experiment was designed by a factorial analysis of variance (Anova). The first factor is control without any treatment (P0), carcass immersion in 3% acetic acid solution (P1), carcass immersion in 3% citric acid (P2), and carcass immersion in combination of acetic acid solution and citric acid, 1.5% each (P3). The second factor was the time after immersion contain of 3 levels: 0 hours (W1), 4 hours (W2), and 8 hours (W3). Data were analyzed statistically by analysis of variance. Broiler carcass immersed in acetic acid and citric acid solution as well as the time of application showed no difference effect on protein content (P0.05). In conclusioin, acetic acid, citric acid, and the time after dipping reaching 8 hours did not affect the protein content of broiler meat. ____________________________________________________________________________________________________________________ Key words: broiler carcass , citric acid 3%, acetic acid 3%, protein content